iDobi: IoT integrated self-service washing machine reservation system with code based booking token / Muhammad Zakwan Hilmi Ismail, Noor Ashitah Abu Othman and Mohd Hafifi Mohd Supir - Ismail, Muhammad Zakwan Hilmi; Abu Othman, Noor Ashitah; Mohd Supir, Mohd Hafifi (College of Computing, Informatics, and Mathematics, 2024)
The iDobi project addresses the common challenges of waiting in queues and queue jumping in self-service laundry facilities by introducing an IoT-integrated reservation system with a code-based booking token. Peak-hour demand for laundry machines is efficiently managed through advance bookings, ensuring a seamless and secure process. The implementation of IoT technology provides real-time updates on machine availability, reducing waiting times and enhancing overall user experience. The project follows the waterfall methodology, resulting in successful functionality tests, including connectivity, user interaction, and responsiveness assessments. Despite hardware limitations leading to the removal of some features like the locking mechanism, the system performs well in integration tests with the ESP8266 microcontroller and real-time queue updates. However, future improvements could involve cloud hosting, real- time queue display, additional washing machines, a locking mechanism, and the integration of a payment gateway, paving the way for a comprehensive and efficient self-service laundry solution. The iDobi project represents a significant step towards enhancing the user experience and addressing the challenges faced in self-service laundry facilities.